Possibilities in using skin texture based image registration for movement analysis - Holmberg, B.; Nordin, B.; Bengtsson, E.; Lanshammar, H. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
The focus of this investigation is if image registration can be achieved between different images of skin on the lower legs of humans. The purpose of the registration is to retrieve information of the movements in the image. Initially this movement is in 2D but further studies will focus more on stereo possibilities and 3D analysis. The 2D image registration shows good promise when using high quality image data of skin and when using low quality image data of more pronounced texture. Further investigations will show if skin based registration can also be used on images of typical video quality.